Interleukin-6 Role in Systemic Inflammation in Rheumatoid Arthritis Iraqi Patients With T2DM - Mahdi, Zena Abdul-Ameer (Jour Med Resh and Health Sci, 2024)
Background: Rheumatoid arthritis (RA) and diabetes mellitus (DM) are chronic conditions associated with significant morbidity. Aim of study: This study amid to investigate the impact of interleukin-6 (IL6) and the relationship between inflammatory markers, glycemic control, and disease characteristics. Methods: A cross-sectional study was conducted on 100 patients (64 with RA only and 34with RA+DM). The sample was collected between June 2023 and January 2024 from the Rheumatology Clinics at the Out-Patient Department of Imam Al-Hussain Medical City in Karbala, Iraq. Serum levels of IL-6, C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), Glycated hemoglobin (HbA1c), and fasting blood sugar (FBS) were assessed as indicators of glycemic control. Demographic data and disease duration were also recorded. Statistical analyses were done by using SPSS version 29. Results: The result of current study revealed that there is a significant difference in IL-6 level between RA (65.53 ± 18.69) and RA+DM (120.36 ± 23.55) groups (p<0.001). A strong positive correlation was observed between HbA1c and IL-6 (r=0.72, p<0.001). There is a significant increased level of IL-6 in female compared to male in RA+DM group (124.84 ± 24.03). The levels of IL-6 correlated positively and significantly with RA duration (r=0.54, p<0.01). Conclusion: This study demonstrates a complex interplay between RA, DM, and systemic inflammation. The presence of DM in RA patients is associated with heightened inflammatory responses, while poor glycaemic control correlates with increased inflammation. These findings underscore the importance of managing both conditions concurrently and suggest that inflammatory markers, particularly IL-6, may serve as useful indicators for assessing disease severity and comorbidity risk in RA patients.